La transmission des amorces saisonnières des troubadours aux trouvères : l’hypothèse des mécanismes émotionnels - Guillaume Oriol (Revue des Langues Romanes)
The seasonal onsets, which are written as and considered to be topos of the poetic composition, don’t only provide us with information about the ways the natural motif moves along between the poetry of the troubadours and of the northerners, but also about the ability of those introductory sequences to include the lover’s emotional leaning. The emotional scripts, on which his love path is based the foundations of his love path, enable us to analyze how the seasonal topos has been conveyed within the poetic tradition. The introductions dedicated to seasonal descriptions, while being a prelude to the topic of love, embody the romantic point of reference where the poet stands. By making the subject matter of the seasonal topos vary, the troubadours, and later on the trouvères, give an emotional signature to the articulation of affectivity in poems. The delicate experience of these beginnings and the expression of feelings have set the continuation from the former to the latter. The variations and recognized continuations, in both ways, make it possible to draw an emotional cartography of the stylistic signatures.